Media Biblio Education Based on Identification of Maladjusment Counseling REBT - Kurniawati, Elvia (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
This research is motivated by the fact that there are several children who have problems such as self-destructive, like to blame others, procrastinate on work and have no tolerance. This study aims to describe the maladjustment behavior of REBT counseling in terms of three indicators and to test the theoretically acceptable educational biblio media. This type of research is research and development. The population of this research is all AKL Department at SMK Negeri 1 Bungo Jambi totaling 122 people with a total sample of 55 people selected using proportional random sampling technique. The research data was obtained through a questionnaire and processed using the percentage technique. The results of the study on the maladjustment model of the REBT counseling approach, based on the identification of maladjustments, showed that there were 29 maladjustments students with a percentage of 52.73% who had many categories of maladjustments. Then after the media testing was carried out on three theoretical experts with the results of the validity of the media being accepted theoretically and suitable to be used to overcome adolescent maladjustment